K− 3He and K− 4He interactions at low energies - Grishina V.Yu. (EPJ Web of Conferences, 2010)
Using the multiple scattering approach (MSA) in the ﬁxed center approximation we calculated the K− 4He and K− 3He scattering lengths. The K− 4He scattering length is also analyzed in the optical potential model. Within the MSA the K− 3He ﬁnal state interaction factor was also calculated. It is found that the K− 3He mass spectrum for the pd → 3HeK+ K− reaction is expected to be inﬂuenced by the K− 3He FSI eﬀect.